The Selective Fossilization Hypothesis, Focus on Form, and the Second Language Classroom: Future Possibilities - Charles Homer Combs (Working Papers in Applied Linguistics and TESOL, 2015)
The questions of how and when (if at all) to treat the potentially fossilizable linguistic features in the second language (L2) classroom have occupied second language researchers and practitioners since Selinker (1972) brought the concept of fossilization to the fore.